From NEET to ‘NIITO’: Defining Social Problem in Japan - Rima Novita Sari; Herlina Sunarti; Ni Luh Suparwati (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This research aims to denote the phrase NEET, which became ‘niito’ in Japan. NEET stands for Not in Education, Employment, or Training at its inception and refers to social problems faced by productive forces who are not in education or employment. NEET has developed into a social problem in many other countries, and the word was later renamed ‘niito’ in Japan. According to the data collected, the term NEET in Japan morphed which spawned a variety of additional ‘niito’ that are not only related to the workforce but also individual psychological and mental health concerns. The method of research is qualitative with descriptive analysis. The social problems theory by Richard C. Fuller dan Richard R. Myers (1941) used to find the answer; demonstrates three steps of the problems which are awareness, policy determination and reform. As results of the research, NEET in Japan originally denoted the phrase productive forces solely did not wish to work. However, as the term evolved in society, it gave rise to various ‘niito’ meanings. Thus, in Japan, the term NEET refers to labor force concerns and individual psychological disorders that can contribute to a person becoming ‘niito’.